2019
DOI: 10.33963/kp.15011
|View full text |Cite
|
Sign up to set email alerts
|

The rationale and design of the LATTEE registry – the first multicenter project on the Scientific Platform of the “Club 30” of the Polish Cardiac Society

Abstract: Introduction Since its establishment 25 years ago, the "Club 30" of the Polish Cardiac Society has gathered young Polish scientists with meaningful achievements in cardiology. 1 The "Club 30" Scientific Platform has been created to facilitate initiation of and participation in multicenter studies among its users, and to promote integration of scientific community. 2 Multicenter cooperation, empowered by the platform, results in an increase in the number of enrolled patients and, consequently, enhances research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Patients treated with apixaban more often received reduced doses (29%) compared to patients on rivaroxaban (14%) and dabigatran (17%; p < 0.01 for both comparisons; Figure 1 B). Patients on apixaban were older, more often had non-paroxysmal AF, had more comorbidities with higher median CHA 2 DS 2 -VASc score (4 [ 2 , 3 , 4 , 5 ] for apixaban vs. 3 [ 2 , 3 , 4 ] for rivaroxaban and 3 [ 1 , 2 , 3 , 4 ] for dabigatran; p < 0.01), had lower GFR, and more often a history of bleeding and anemia, and were more often treated with antiplatelets compared to patients on other NOACs ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients treated with apixaban more often received reduced doses (29%) compared to patients on rivaroxaban (14%) and dabigatran (17%; p < 0.01 for both comparisons; Figure 1 B). Patients on apixaban were older, more often had non-paroxysmal AF, had more comorbidities with higher median CHA 2 DS 2 -VASc score (4 [ 2 , 3 , 4 , 5 ] for apixaban vs. 3 [ 2 , 3 , 4 ] for rivaroxaban and 3 [ 1 , 2 , 3 , 4 ] for dabigatran; p < 0.01), had lower GFR, and more often a history of bleeding and anemia, and were more often treated with antiplatelets compared to patients on other NOACs ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The Left Atrial Thrombus on Transesophageal Echocardiography (LATTEE) registry (NCT03591627) was a prospective, observational study enrolling consecutive patients with AF or AFl in whom TEE was performed before direct current cardioversion or catheter ablation, hospitalized in 13 cardiology departments (11 academic centers and two territorial departments) in Poland. Details on the study rationale and design have been reported elsewhere [ 5 ]. The patient recruitment process started in November 2018 in the coordinating centre and lasted 12 months since the beginning of the study in each participating centre or longer, i.e., until the inclusion of at least 200 patients at each participating centre (with the last patient enrolled in May 2020).…”
Section: Methodsmentioning
confidence: 99%
“…In total, 3,109 AF or AFl patients were included in the study. Detailed data about the entire LATTEE registry group were included in previous manuscripts ( 9 , 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…The reasons for admission were catheter ablation or cardioversion and TEE performed directly before the procedure. The methods of the study were previously described in detail ( 9 , 10 ). Briefly, consecutive hospitalized patients diagnosed with AF/AFl who underwent TEE before direct current cardioversion or catheter ablation were included in the registry.…”
Section: Methodsmentioning
confidence: 99%
“…It is worth mentioning that both departments are participating in a new Polish multicenter prospective registry called Left Atrial Thrombus on TEE (LATEE). This study hopes to analyze the larger groups of patients contained in this registry, especially for the optimal management of LAA thrombus or sludge [29].…”
Section: Discussionmentioning
confidence: 99%